Preparation method of high-safety composite lithium metal negative electrode and negative electrode interface derived solid-state battery

Through the preparation method of composite lithium metal negative electrode, the alloy layer is formed by the interaction between the polymer film modified with polar functional groups and the metal layer X, combined with the integrated manufacturing method, the solid electrolyte is grown in situ, which solves the problems of uneven lithium deposition and mechanical powderization of the lithium metal negative electrode during the circulation process, and significantly improves the cycle stability and safety of the battery.

CN119601603AActive Publication Date: 2025-03-11HARBIN INST OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411781712.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

During the circulation process, the lithium metal negative electrode has problems such as uneven lithium deposition and mechanical powderization, resulting in safety risks and unstable electrochemical performance.

Method used

The preparation method of a high-safe composite lithium metal negative electrode is adopted to combine lithium metal, metal X and polymer base film, and the interaction between the polymer film modified with polar functional groups and the metal layer X is formed to form an alloy layer, improve the mechanical and chemical stability of the electrode, and grow solid electrolyte in situ on the negative electrode side through an integrated manufacturing method to achieve a close bond between the negative electrode and the solid electrolyte interface.

Benefits of technology

The cycling stability and safety of the lithium metal negative electrode is significantly improved, the lithium metal powderization is slowed down, the interface resistance between the electrode and the electrolyte is reduced, the continuity of ion transmission is ensured, and the long-term circulation performance and thermal safety of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601603A_ABST
    Figure CN119601603A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-safety composite lithium metal negative electrode and a negative electrode interface derived solid-state battery, the high-safety composite lithium metal negative electrode is formed by compounding lithium metal, metal X and a polymer basement membrane, and the polymer basement membrane is a polymer membrane modified by a polar functional group, the polar functional group and the metal layer X have relatively strong interaction, the polar functional group is used as a molecular welding agent to anchor the metal layer, and the lithium metal and the metal layer X spontaneously form an alloy layer, so that the chemically connected multi-layer composite lithium metal negative electrode is obtained, and the problem of mechanical pulverization of the lithium metal in the long-term cycle process is favorably improved. The invention provides an innovative solid-state battery preparation strategy, and the formation of the solid-state electrolyte is directly promoted on the negative electrode side through the catalytic action of the alloy compound, so that the tight combination of the negative electrode and the solid-state electrolyte interface is realized. By optimizing material selection and a preparation process, the performance of the solid-state battery can be further improved, and the ever-increasing energy storage requirement is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials, and relates to a method for preparing a lithium metal negative electrode and a solid-state battery, and specifically to a method for preparing a stable lithium metal negative electrode with ion / electron transmission continuity and a high-safety solid-state battery. Background Art

[0002] As the global demand for efficient energy storage systems continues to rise, the research and development of rechargeable battery technology should focus on improving energy density and ensuring safety. Lithium metal anode has excellent specific capacity (3861mAh g -1 ) and extremely low electrochemical potential (-3.041V vs. standard hydrogen electrode), it is considered to be an ideal choice for the next generation of battery anode materials, which can meet the needs of future batteries in terms of energy density, cycle life and cost-effectiveness. However, lithium metal anodes face the problem of volume expansion and contraction during the deposition and stripping of lithium ions, which may lead to mechanical pulverization of electrode materials. During the deposition and stripping of lithium, the formation of lithium dendrites not only accelerates the decomposition of the electrolyte, but also may cause poor contact between lithium metal filaments, resulting in cracks or gaps. In addition, the moss-like growth of lithium dendrites increases its surface area, thereby exacerbating the reactivity with oxygen and causing serious safety risks.

[0003] To solve this problem, many recent design strategies, such as adjusting the artificial construction of solid electrolyte interface membranes, optimizing electrolyte formulations, developing solid electrolytes, and designing three-dimensional current collectors, can inhibit the growth of lithium dendrites and improve the electrochemical performance of lithium metal batteries to a certain extent. However, it is difficult to achieve excellent (electro)chemical stability, mechanical stability, and uniform and rapid ion transport at the same time, and there is still a certain gap from practical application. Therefore, designing efficient and stable composite lithium metal electrodes is of great significance for improving the cycle performance and safety performance of lithium metal batteries. Summary of the invention

[0004] In view of the safety issues caused by uneven lithium deposition and lithium metal pulverization of lithium metal negative electrodes during the cycle, the present invention provides a method for preparing a high-safety composite lithium metal negative electrode and a negative electrode interface-derived solid-state battery. The high-safety composite lithium metal negative electrode prepared by the present invention is composited with lithium metal, metal X and a polymer substrate film. The polymer substrate film is a polymer film modified with polar functional groups. There is a strong interaction between the polar functional groups and the metal layer X. As a molecular welding agent, the metal layer is anchored. The lithium metal and the metal layer X spontaneously form an alloy layer, thereby obtaining a chemically connected multilayer composite lithium metal negative electrode, which helps to improve the problem of mechanical pulverization of lithium metal during long-term cycles. The present invention proposes an innovative solid-state battery preparation strategy, which involves an integrated manufacturing method for in-situ growth of solid electrolytes using composite lithium metal negative electrodes. Through the catalytic action of alloy compounds, the formation of solid electrolytes is directly promoted on the negative electrode side, thereby achieving a close combination of the negative electrode and the solid electrolyte interface. This integrated preparation process not only significantly reduces the interface resistance between the electrode and the electrolyte, but also ensures the continuity of ion transmission, regulates the uniformity of lithium ion deposition, and inhibits the formation of lithium dendrites, which is crucial to improving the cycle stability and safety of solid-state batteries. In addition, the present invention also demonstrates its application potential in extreme environments and provides a new direction for the development of high-performance energy storage devices in the future. By optimizing material selection and preparation processes, the present invention can further improve the performance of solid-state batteries and meet the growing demand for energy storage.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A method for preparing a high-safety composite lithium metal negative electrode, the high-safety composite lithium metal negative electrode comprising a lithium metal layer, a metal X layer and a polymer substrate film, wherein: the lithium metal layer and the metal X layer spontaneously form an alloy layer, and the metal X layer and the polymer substrate film are connected through a polar functional group, and the specific preparation steps are as follows:

[0007] Step 1: Preparation of functional group-modified polymer substrate membrane

[0008] Step 1: Special treatment of the functional groups on the surface of the polymer substrate membrane by chemical reaction method: 1-2g of amide monomer is added to a mixed solution of 2-4ml of organic acid and 15-20ml of inorganic acid, and then the mixed solution is added to 100-120ml of deionized water, and the mixture is transferred to a round-bottom flask equipped with a magnetic stirring bar, and vigorously stirred at 10-15°C for 3-8h to form a mixed transparent solution. The purpose of this step is to form a soluble aniline salt by combining the protonated nitrogen-containing functional group with the deprotonated organic acid, wherein:

[0009] The amide monomer is one of aniline, acrylamide and N-hydroxyethyl acrylamide;

[0010] The organic acid is one of phytic acid, humic acid, malic acid and citric acid;

[0011] The inorganic acid solution is hydrochloric acid or sulfuric acid, and its mass fraction is 30-38wt.%;

[0012] Step 1 and 2: Add an initiator to the above-mentioned mixed transparent solution to obtain a preliminary polymerization precursor, and immediately evenly coat the preliminary polymerization precursor on the polymer substrate film, and further initiate the reaction at a temperature of 40 to 70° C. to obtain a polymer substrate film with a surface modified with polar functional groups. The purpose of this step is to improve the mechanical strength of the polymer substrate film through further polymerization reaction, wherein:

[0013] The initiator is one of ammonium persulfate, potassium persulfate, etc., and its addition amount is 0.2-1% of the mass of the amide monomer;

[0014] The polymer substrate film is one or more combinations of polyvinylidene fluoride (PVDF), polyamideimide (PAI), polyetherimide (PEI), polyethylene naphthalate (PEN), polyethylene terephthalate (PET), polyimide (PI), and polystyrene (PS);

[0015] Step 13: Place the polymer substrate membrane with a surface modified with polar functional groups obtained in step 12 in a vacuum oven and dry it to obtain a functional group-modified polymer substrate membrane, wherein:

[0016] The drying temperature is 100-110°C and the drying time is 12-20h;

[0017] The thickness of the functional group modified polymer substrate film is 5 to 80 μm;

[0018] Step 2: Preparation of Metal X Layer

[0019] A metal X layer is deposited on the functional group-modified polymer substrate film obtained in step 1, thereby obtaining a polymer substrate film to which the metal X layer is attached. The metal X layer and the organic acid polar functional group have a strong interaction (metal X…O), which is beneficial to increase the bonding strength between the alloy layer and the substrate film, thereby ensuring the stability and continuity during the electrode cycle process and preventing safety problems caused by pulverization during long-term cycles, wherein:

[0020] The metal X is a metal that can react with metallic lithium to form an alloy, specifically one of silver, aluminum, gallium, zinc, germanium, tin, etc.;

[0021] The method of depositing the metal X layer is vacuum evaporation, gas sublimation, physical vapor deposition, solution reaction, plasma etching, liquid metal filling, etc.;

[0022] The thickness of the metal X layer is 0.5 to 4 μm;

[0023] Step 3: Preparation of multilayer composite lithium metal anode

[0024] A composite of metallic lithium and polymer-metal X layer is prepared by a composite method, and the metallic lithium spontaneously reacts with the metal X layer in step 2 to form an alloy layer, thereby obtaining a multilayer composite lithium metal negative electrode, wherein:

[0025] The composite method is one of a chemical mechanical method, an electrodeposition method, a mechanical rolling method, an evaporation method, a chemical reaction method, etc.;

[0026] The thickness of the multi-layer composite lithium metal negative electrode is 10 to 50 μm.

[0027] A method for preparing a negative electrode interface-derived solid-state battery comprises the following steps:

[0028] Step 1: Take a certain amount of electrolyte No. 1 solvent and electrolyte No. 2 solvent and mix them, immediately add the additive to the mixed solvent, then add a certain amount of lithium salt, stir at room temperature for 2 to 6 hours, and prepare an electrolyte mixed solution, wherein:

[0029] The electrolyte solvent No. 1 is one of 1,3-dioxolane (DOL), tetrahydrofuran (THF), dimethyltetrahydrofuran (MeTHF), fluoroethylene carbonate (FEC), ethylene carbonate (EC), and propylene carbonate (PC);

[0030] The electrolyte No. 2 solvent is a mixture of ethylene glycol dimethyl ether (DME), ethylene glycol dibutyl ether (EGDE), n-butyl methyl ether (MNBE), diethyl carbonate (DEC), and dimethyl carbonate (DMC);

[0031] The volume ratio of the electrolyte No. 1 solvent to the electrolyte No. 2 solvent is 2-8:8-2;

[0032] The additive is one of lithium nitrate, lithium bis(trimethylsilyl)amide, hexamethyldisilazane, trimethylsilyl isocyanate, and thiocyanic acid, and the amount added is 0.1-1wt.% of the mass of the electrolyte mixed solution;

[0033] The lithium salt is one or more of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium hexafluoroarsenate (LiAsF6), and the concentration of the lithium salt is 0.6 to 3M;

[0034] Step 2: In a glove box, take the multilayer composite lithium metal obtained in the above step 3 as the negative electrode, drip 10 to 25 μL of the electrolyte mixed solution prepared in step 1 on the side containing the alloy layer, use the commercial active material as the positive electrode, and then place it at a temperature of 30 to 60 ° C for 4 to 10 hours to obtain a solid-state battery. The purpose of this step is to initiate the polymerization reaction of the electrolyte solution through the Lewis acidity of the alloy, obtain a solid electrolyte derived from the negative electrode alloy interface, and realize the integrated preparation of the negative electrode and the electrolyte, wherein:

[0035] The positive electrode is lithium cobalt oxide, lithium-rich manganese-based, nickel cobalt manganese oxide (such as LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.83 Co 0.05 Mn 0.12 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2) etc.

[0036] Compared with the prior art, the present invention has the following advantages:

[0037] 1. The composite lithium metal negative electrode prepared by the present invention creatively uses the polar functional groups in the organic acid as the molecular welding agent of the alloy layer and the polymer substrate film to ensure the high continuity of the electrode during the cycle, which plays a key role in slowing down the pulverization of lithium metal and effectively prevents the safety risks caused by it, which is crucial for the practical application of high-capacity negative electrode materials. In addition, the anti-corrosion properties of the organic acid solution also significantly improve the compatibility of the electrode and electrolyte interface, thereby enhancing the long-term cycle stability of the battery.

[0038] 2. The polymer base film introduced in the present invention has high thermal stability and flame retardant properties, can effectively block heat transfer under extreme conditions such as thermal runaway of the battery cell, exhibits better cycle stability and thermal safety under practical test conditions, prevents the occurrence of thermal runaway, and can reduce the weight of the battery to a certain extent and improve the battery energy density.

[0039] 3. The preparation method of the interface-derived electrolyte introduced in the present invention can be extended to other alkali metal batteries, greatly improving the interface compatibility of solid-state batteries, improving the interface charge transfer kinetics, and promoting the operation of solid-state batteries at low temperatures. More importantly, the interface alloy component dissolves the contacted dendrites through reaction, effectively preventing the further growth of the dendrites and preventing the complete failure of the battery.

[0040] 4. The present invention is applicable to large-scale production and provides a feasible approach for the large-scale application of high-safety lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Schematic diagram of the preparation process of composite lithium metal negative electrode;

[0042] Figure 2 This is the SEM of the composite lithium metal negative electrode prepared in Example 1;

[0043] Figure 3 Impedance test of lithium symmetric batteries assembled for Example 1 and Comparative Example 1;

[0044] Figure 4 Long cycle test of lithium symmetric batteries assembled for Example 1 and Comparative Example 1;

[0045] Figure 5 This is a schematic diagram of the solid-state battery structure;

[0046] Figure 6 Long cycle test of the full battery assembled for Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0047] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0048] Example 1

[0049] This embodiment provides a method for preparing a highly safe composite lithium metal negative electrode, such as Figure 1 As shown, the method comprises the following steps:

[0050] Step 1: Preparation of functional group-modified polymer substrate membrane

[0051] Step 1: Use chemical reaction method to perform special functional group treatment on the surface of polymer substrate membrane: add 1g aniline to a mixed solution of 3ml phytic acid and 16ml hydrochloric acid, add it to 100ml deionized water, and then transfer the mixture to a round-bottom flask equipped with a magnetic stirring bar, and vigorously stir for 4h at 10°C to form a mixed transparent solution. The purpose of this step is to form a soluble aniline salt by combining the protonated nitrogen-containing functional group with the deprotonated organic acid. The mass fraction of the hydrochloric acid is 30wt.%.

[0052] Step 1 and 2: Add 0.2% of the mass of aniline monomer as initiator ammonium persulfate to the above-mentioned mixed transparent solution to obtain a preliminary polymer precursor, and immediately and evenly coat it on the polyamide-imide (PAI) substrate film, and further initiate the polymerization reaction at a temperature of 70°C. A polymer substrate film with high mechanical strength and modified with polar functional groups in the polymer chains is obtained by further cross-linking the macromolecular polymer chains. The polymer substrate film is further placed in a vacuum oven and dried at 100°C for 15 hours, and the thickness of the obtained polymer substrate film is 20 μm.

[0053] Step 2: Preparation of metal germanium layer

[0054] The metal germanium was deposited on the surface of the polymer substrate film by vacuum evaporation: at 5.8×10 -3 Under a vacuum state of 1.5 Pa, metal germanium particles with a purity of 99.9% are placed in a crucible, heated to melt and continuously heated until vaporized, and the functional group-modified polymer substrate film obtained in step 1 is placed under the vacuum state, and the vaporized metal particles are rapidly deposited on the polymer substrate film in a linear motion without collision, and after repeated vacuum coating, a metal germanium layer with a thickness of 2.5 μm is formed on the surface of the polymer substrate film. Based on the chelation effect of the polar functional groups in phytic acid and the metal (metal X…O), the metal germanium layer and the polymer film generate a strong interaction force, which increases the bonding strength of the metal layer and the substrate film, thereby ensuring the stability and continuity during the electrode cycle and preventing safety problems caused by pulverization during long-term cycles.

[0055] Step 3: Preparation of multilayer composite lithium metal anode

[0056] The composite of metallic lithium and polymer-metal germanium was prepared by a simple and easy rolling method. The rolled metallic lithium formed an alloy layer with metallic germanium through a spontaneous alloying reaction to prepare a multi-layer composite lithium metal negative electrode. The SEM image is shown in Figure 2 As shown. The thickness of the lithium metal negative electrode is 20 μm. The composite lithium metal negative electrode prepared in this embodiment has a lower interface impedance. Its impedance at different temperatures is shown as follows: Figure 3 As shown. It is assembled into a symmetrical battery and tested for long cycle stability. Figure 4 shown.

[0057] This embodiment also provides a method for preparing an interface-derived solid-state battery, wherein the solid-state battery comprises a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode comprises the negative electrode material described above, and the electrolyte is prepared by deriving the negative electrode material, and the specific steps are as follows:

[0058] Step 1: In a glove box, take 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) solvents, mix them in a volume ratio of 7:3, immediately add 0.2% of the electrolyte mass of the additive bis(trimethylsilyl)amide lithium, then add a certain amount of lithium salt LiFSI, stir at room temperature for 3 hours, and form an electrolyte mixed solution with a concentration of 1.4M.

[0059] Step 2: In a glove box, take the multilayer composite lithium metal obtained in step 3 as the negative electrode, drip 15 μL of the electrolyte mixed solution prepared in step 1 on the side containing the alloy layer, and use commercial active material lithium cobalt oxide as the positive electrode package, then place it at a temperature of 50°C for 4 hours to react to obtain a solid-state battery, the structural diagram of which is shown in the figure. Figure 5 The purpose of this step is to initiate the polymerization reaction of the electrolyte solution through the Lewis acidity of the alloy, obtain a solid electrolyte derived from the negative electrode alloy interface, and realize the integrated preparation of the negative electrode and the electrolyte, further improving the interface compatibility problem of the solid-state battery. Figure 6 The excellent long-cycle stability shown proves that the solid-state battery assembled with the multilayer composite lithium metal anode prepared in this embodiment is superior to the conventional lithium metal anode.

[0060] Embodiment 2:

[0061] This embodiment provides a method for preparing a highly safe composite lithium metal negative electrode, such as Figure 1 As shown, the method comprises the following steps:

[0062] Step 1: Preparation of functional group-modified negative electrode substrate membrane

[0063] Step 1: Use chemical reaction method to perform special functional group treatment on the surface of polymer substrate: add 1g N-hydroxyethyl acrylamide to a mixed solution of 4ml phytic acid and 20ml hydrochloric acid, add it to 100ml deionized water, transfer the mixture to a round-bottom flask equipped with a magnetic stirring bar, and stir vigorously at 15°C for 7h to form a mixed transparent solution. The mass fraction of the hydrochloric acid is 30wt.%.

[0064] Step 1 and 2: add ammonium persulfate, an initiator accounting for 0.2% of the mass of N-hydroxyethyl acrylamide monomer, to the above-mentioned mixed transparent solution to obtain a preliminary polymer precursor, and immediately and evenly coat it on a polyamideimide (PAI) substrate film, further initiate a polymerization reaction at a temperature of 70°C, and obtain a polymer substrate film with high mechanical strength and surface modification containing polar functional groups through further cross-linking of macromolecular polymer chains. The polymer substrate film is further placed in a vacuum oven and dried at 100°C for 10 hours, and the thickness of the obtained polymer substrate film is 12 μm.

[0065] Step 2: Preparation of a metal aluminum layer attached to the surface of the base film

[0066] The polymer substrate membrane was placed in a 99.99% pure gaseous aluminum chloride solution at a concentration of 3.5 g L -1 A metal aluminum layer with a thickness of 2 μm is formed on the surface of the polymer substrate film at a temperature of 178°C. The amount of the deposited metal aluminum layer can be controlled by controlling the exposure time. After cooling, the polymer substrate film with the metal aluminum layer attached can be obtained.

[0067] Step 3: Preparation of multilayer composite lithium metal anode

[0068] The composite of metal lithium and polymer-metal aluminum is prepared by a simple rolling method. The rolled metal lithium forms an alloy layer with metal aluminum through a spontaneous alloying reaction to prepare a multi-layer composite lithium metal negative electrode. The thickness of the lithium metal negative electrode is 25 μm.

[0069] This embodiment also provides a method for preparing an interface-derived solid-state battery, wherein the solid-state battery comprises a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode comprises the negative electrode material described above, and the electrolyte is prepared by deriving the negative electrode material, and the specific steps are as follows:

[0070] Step 1: Take 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) solvents, mix them in a volume ratio of 7:3, immediately add 0.2% of the electrolyte mass of trimethylsilyl isocyanate additive, then add a certain amount of lithium salt LiFSI, stir at room temperature for 3 hours, and form an electrolyte mixed solution with a concentration of 1.4M.

[0071] Step 2: In a glove box, take the multilayer composite lithium metal obtained in the above step 3 as the negative electrode, drip 10 μL of the electrolyte mixed solution prepared in step 1 on the side containing the alloy layer, and encapsulate it with commercial active material lithium cobalt oxide as the positive electrode, and then place it at a temperature of 50°C to react for 4 hours to obtain a solid-state battery.

[0072] Embodiment 3:

[0073] The difference between this embodiment and embodiment 1 is that the selected polymer substrate film is polyimide (PI).

[0074] Embodiment 4:

[0075] The difference between this embodiment and embodiment 1 is that the specific steps of the interface-derived solid-state battery are as follows:

[0076] Step 1: Take ethylene carbonate (EC) and dimethyl carbonate (DMC) solvents, mix them in a volume ratio of 5:2, and then introduce a certain amount of lithium salt LiFSI to form an electrolyte mixed solution with a concentration of 2M.

[0077] Step 2: In a glove box, take a multilayer composite lithium metal as the negative electrode, drop 10 μL of the electrolyte mixed solution prepared in step 1 on the side containing the alloy layer, and use commercial active material lithium nickel cobalt manganese oxide (such as LiNi 0.8 Co 0.1 Mn 0.1 O2) is used as the positive electrode to assemble a battery, which is then placed at 50°C for 4 hours to obtain a solid-state battery.

[0078] Embodiment 5:

[0079] The difference between this embodiment and embodiment 1 is that the composite method of the lithium metal negative electrode in step 3 is an electrochemical deposition method.

[0080] Comparative Example 1:

[0081] The difference between this comparative example and Example 1 is that the negative electrode material selected is a lithium copper composite strip with a thickness of 50 μm. The test results are as follows: Figure 3 , Figure 4 and Figure 6 shown.

[0082] Comparative Example 2:

[0083] The difference between this comparative example and Example 1 is that there is no step of preparing the integrated negative electrode of the interface-derived electrolyte, and the conventional polymer solid electrolyte is directly used to assemble the battery.

Claims

1. A method for preparing a high-safety composite lithium metal negative electrode, characterized in that The method comprises the following steps: Step 1: Preparation of functional group-modified polymer substrate membrane Step 1: Special treatment of the functional groups on the surface of the polymer substrate membrane by chemical reaction method: 1-2 g of amide monomer is added to a mixed solution of 2-4 ml of organic acid and 15-20 ml of inorganic acid, and then the mixed solution is added to 100-120 ml of deionized water, and the mixture is transferred to a round-bottom flask equipped with a magnetic stirring bar, and vigorously stirred at 10-15° C. for 3-8 hours to form a mixed transparent solution; Step 1 and 2, adding an initiator to the above-mentioned mixed transparent solution to obtain a preliminary polymerization precursor, and immediately coating the preliminary polymerization precursor evenly on the polymer substrate film, further initiating the reaction at a temperature of 40 to 70° C. to obtain a polymer substrate film with a surface modified with polar functional groups; Step 13: placing the polymer substrate membrane with a surface modified with polar functional groups obtained in step 12 in a vacuum oven for drying to obtain a functional group-modified polymer substrate membrane; Step 2: Preparation of Metal X Layer Depositing a metal X layer on the functional group-modified polymer substrate film obtained in step 1, thereby obtaining a polymer substrate film with the metal X layer attached, wherein: the metal X is a metal that can react with metallic lithium to form an alloy; Step 3: Preparation of multilayer composite lithium metal anode A composite of metallic lithium and polymer-metal X layer is prepared by a composite method. The metallic lithium and the metal X layer in step 2 undergo a spontaneous chemical reaction to form an alloy layer, thereby obtaining a multilayer composite lithium metal negative electrode.

2. The method for preparing a high-safety composite lithium metal negative electrode according to claim 1, characterized in that In the step 1, the amide monomer is one of aniline, acrylamide, and N-hydroxyethyl acrylamide; the organic acid is one of phytic acid, humic acid, malic acid, and citric acid; and the inorganic acid solution is hydrochloric acid or sulfuric acid, and its mass fraction is 30 to 38 wt.%.

3. The method for preparing a high-safety composite lithium metal negative electrode according to claim 1, characterized in that In steps one and two, the initiator is one of ammonium persulfate and potassium persulfate, and the added amount is 0.2-1% of the mass of the amide monomer; the polymer base film is one or more combinations of polyvinylidene fluoride, polyamideimide, polyetherimide, polyethylene naphthalate, polyethylene terephthalate, polyimide, and polystyrene.

4. The method for preparing a high-safety composite lithium metal negative electrode according to claim 1, characterized in that In the steps 1 to 3, the drying temperature is 100 to 110° C. and the drying time is 12 to 20 hours; the thickness of the functional group-modified polymer substrate film is 5 to 80 μm.

5. The method for preparing a high-safety composite lithium metal negative electrode according to claim 1, characterized in that In the step 2, the metal X is one of silver, aluminum, gallium, zinc, germanium, and tin; the method for depositing the metal X layer is one of vacuum evaporation, gas sublimation, physical vapor deposition, solution reaction, plasma etching, and liquid metal filling; the thickness of the metal X layer is 0.5 to 4 μm.

6. The method for preparing a high-safety composite lithium metal negative electrode according to claim 1, characterized in that In the step three, the composite method is one of a chemical mechanical method, an electrodeposition method, a mechanical rolling method, a vapor deposition method, and a chemical reaction method; and the thickness of the multilayer composite lithium metal negative electrode is 10 to 50 μm.

7. A high-safety composite lithium metal negative electrode prepared by the method according to any one of claims 1 to 6.

8. A method for preparing a negative electrode interface-derived solid-state battery, characterized in that The method comprises the following steps: Step 1: Take a certain amount of electrolyte No. 1 solvent and electrolyte No. 2 solvent and mix them, immediately add the additive to the mixed solvent, then add a certain amount of lithium salt, stir at room temperature for 2 to 6 hours, and prepare an electrolyte mixed solution, wherein: the volume ratio of the electrolyte No. 1 solvent and the electrolyte No. 2 solvent is 2 to 8:8 to 2, and the concentration of the lithium salt is 0.6 to 3M; Step 2: In a glove box, take the multilayer composite lithium metal prepared by the method described in any one of claims 1 to 6 as the negative electrode, drip 10 to 25 μL of the electrolyte mixed solution prepared in step 1 on the side containing the alloy layer, use the commercial active material as the positive electrode, and then place it at a temperature of 30 to 60°C to react for 4 to 10 hours to obtain a solid-state battery.

9. The method for preparing a negative electrode interface derived solid-state battery according to claim 8, characterized in that In the step 1, the electrolyte solvent No. 1 is one of 1,3-dioxolane, tetrahydrofuran, dimethyltetrahydrofuran, fluoroethylene carbonate, ethylene carbonate, and propylene carbonate; the electrolyte solvent No. 2 is a mixture of ethylene glycol dimethyl ether, ethylene glycol dibutyl ether, n-butyl methyl ether, diethyl carbonate, and dimethyl carbonate; the additive is one of lithium nitrate, lithium bis(trimethylsilyl)amide, hexamethyldisilazane, trimethylsilyl isocyanate, and thiocyanic acid, and the added amount is 0.1-1wt.% of the mass of the electrolyte mixed solution; the lithium salt is one or more combinations of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, bis(fluorosulfonyl)imide lithium salt, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl)imide, and lithium hexafluoroarsenate.

10. The method for preparing a negative electrode interface derived solid-state battery according to claim 8, characterized in that In step 2, the positive electrode is one of lithium cobalt oxide, lithium-rich manganese-based, and nickel-cobalt-manganese-based lithium.

Citation Information

Patent Citations

  • Lithium metal cathode coated with solid polymer electrolyte and preparation method thereof

    CN108511687A

  • Method for producing electrode for nonaqueous electrolyte secondary battery

    CN111213263A

  • Composite lithium metal negative electrode material, preparation method thereof and solid-state battery

    CN116666577A

  • Modified lithium metal negative electrode and preparation method and application thereof

    CN117832402A

  • Preparation method and application of silicon-carbon composite negative electrode material

    CN119038528A